Spiritual Leadership impact on Corporate Social Responsibility Mediating by Spiritual Wellbeing: Evidence from the Hospitality Industry of Lahore Pakistan - Siddiq, Muhammad Usman; Rehman, Attique ur; Mahmood, Kashif; Arshad, Arfan (Pakistan Journal of Humanities and Social Sciences, 2023)
The main object is to increase the generalizability of spiritual leadership theory as Fry explain many outcomes of spiritual leadership and one of the outcome he predicted is CSR using this theoretical gap we conducted empirical research. In this study we use quantitative methods in which cross sectional study was done and data was collecting through questionnaire. The place of the study is Lahore Pakistan and evidence is taken from the hospitality industry working in Lahore Pakistan. Questionnaire were filled by the employees working in the hospitality industry and our sample size is 222.Seven hypothesis were proposed and all the hypothesis were accepted in this study. The result expand the spiritual leadership generalizability in term of CSR because this gap is not tested yet by the researcher and out study contributes in the body of knowledge while filling this gap. For future researcher and academicians this research will also help them to understand the spiritual leadership theory and its outcomes and its generalizability.